Design, In Vitro Antimicrobial Evaluation, and In Silico Drug-Likeness Assessment of Novel Pyrazoline Derivatives - Yadav, Alka; Gangwar, Sunita; Singh Rathore, Udai Bhan; Sharma, Neeraj; Sharma, Praveen (Journal of Neonatal Surgery, 2025)
The present study reports the synthesis, In vitro antimicrobial evaluation, and in silico drug-likeness prediction of a novel series of pyrazoline derivatives (4a–4h). Antimicrobial activity was evaluated using the cup plate method against a panel of bacterial and fungal pathogens. The zone of inhibition was measured to assess antibacterial and antifungal efficacy. In silico studies were performed using a Python-based RDKit tool to determine key physicochemical parameters, ADME properties, and toxicity predictions. Compound 4h exhibited the most potent activity against all tested strains. All compounds showed favorable drug-likeness and high gastrointestinal absorption, with no AMES toxicity flags